2022
DOI: 10.1038/s41598-022-18593-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenome of coeliac disease vs. inflammatory bowel disease

Abstract: Coeliac disease (CeD) is characterized by gliadin-induced intestinal inflammation appearing in genetically susceptible individuals, such as HLA-DQ2.5 carriers. CeD, as well as other chronic intestinal disorders, such as Crohn's disease (CD) and ulcerative colitis, has been associated with increased morbidity and mortality, but the causes are unknown. We systematically analysed CeD-associated diagnoses and compared them to conditions enriched in subjects with CD/UC as well as in HLA-DQ2.5 carriers without CeD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Growing evidence indicates that gut microbiome is involved in the pathogenesis of SpA [ 7 ] and AS patients may have a 5.3-fold higher incidence of chronic inflammatory intestinal diseases such as IBD than healthy individuals [ 30 ]. IBD has a partially shared pathogenesis with CeD; in both conditions, genetics and environment contribute to immune dysregulation, leading to chronic inflammation and disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that gut microbiome is involved in the pathogenesis of SpA [ 7 ] and AS patients may have a 5.3-fold higher incidence of chronic inflammatory intestinal diseases such as IBD than healthy individuals [ 30 ]. IBD has a partially shared pathogenesis with CeD; in both conditions, genetics and environment contribute to immune dysregulation, leading to chronic inflammation and disease [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…While in the literature there are many studies regarding the correlation between gut microbiota and CD, fewer studies were drafted about gut microflora and NCGS and its possible role in the disease pathogenesis [ 24 , 43 , 44 ]. At baseline, Garcia-Mazcorro et al found an increased number of Actinobacillus and Ruminococcaceae genera in NCGS patients compared to Celiac ones and a higher rates of Pseudomonas spp.…”
Section: The Impact Of Gluten-free Diet On Gut Microbiota In Gluten R...mentioning
confidence: 99%
“…As we discussed above, gluten might be one of the main players in this interplay due to its role in intestinal inflammation. Indeed, Celiac disease, which is a chronic immune-mediated enteropathy consequent to gluten intake, shares with IBD a multifactorial etiology, resulting from a complex interplay between genetic variability, environmental factors, and dysregulated immune response [ 44 ].…”
Section: Gluten and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…MyHealthyGut (MHG) is a mobile app that was originally designed for celiac disease (CeD) self-management [14,15]. At present, the only treatment for CeD is a strict gluten-free (GF) diet [16]. The app was developed to provide guidance, diet and symptom tracking, and information to users, related to the GF diet and CeD.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…diet [16]. 9 Would you find it useful if patients could share information about their diet and health through the app ahead of appointments?…”
Section: Introductionmentioning
confidence: 99%